Implementasi Inovasi Probiotik Berbasis Limbah Pasar untuk Meningkatkan Produktivitas Ikan Nila di Kelompok Krido Yuwono Mina Padi Technopark, Panembangan, Banyumas - Sujadi, Frentina Murti; Anjaini, Jefri; Simangunsong, Tohap; Setiyaningsih, Lilik; Mardika, Hanisya Putri Kania; Setyawan, Agung Cahyo; Sukardi, Purnama; Kusuma, Baruna; Nurhabib, Asro; Marnani, Sri; Harvinda, Yohanes (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The probiotic innovation training programme based on market waste implemented at the Krido Yuwono Mina Padi Technopark Group aims to increase tilapia productivity and farming efficiency through the use of organic waste as raw material for probiotics. This training involves participants in the production of probiotics through the fermentation of market waste using lactic acid bacteria starters. The evaluation results show an increase in tilapia productivity of around 15-20% with better feed efficiency and a reduction in ammonia levels in pond water, which was previously a major problem in maintaining fish health. The community involved in this programme also increased their confidence in managing tilapia farming efficiently and received new knowledge that can reduce operational costs. This programme has achieved significant social and economic impacts and is expected to develop into a sustainable community empowerment model in the field of aquaculture and support more environmentally friendly waste management.